2012
DOI: 10.1371/journal.pone.0042704
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Promoter Methylation and Expression of UTF1 during Cervical Carcinogenesis

Abstract: Promoter methylation profiles are proposed as potential prognosis and/or diagnosis biomarkers in cervical cancer. Up to now, little is known about the promoter methylation profile and expression pattern of stem cell (SC) markers during tumor development. In this study, we were interested to identify SC genes methylation profiles during cervical carcinogenesis. A genome-wide promoter methylation screening revealed a strong hypermethylation of Undifferentiated cell Transcription Factor 1 (UTF1) promoter in cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…Therefore, new screening modalities with high sensitivity and specificity need to be evaluated and pursued. Toward this, DNA methylation markers can be highly useful in screening early stages of cervical cancer (2,38,39). Hypermethylation of the DOC2B promoter and its low expression during the pre-malignant condition shows its potential as a marker for early screening of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new screening modalities with high sensitivity and specificity need to be evaluated and pursued. Toward this, DNA methylation markers can be highly useful in screening early stages of cervical cancer (2,38,39). Hypermethylation of the DOC2B promoter and its low expression during the pre-malignant condition shows its potential as a marker for early screening of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…; Guenin et al . ). Figure shows representative images of UTF1 staining in each tissue type, with their corresponding negative controls (capital and lower case letters respectively).…”
Section: Resultsmentioning
confidence: 97%
“…; Guenin et al . ). Interestingly, we found that UTF1 expression was not associated with that of Sox2 and Oct4A in any of the epithelial cell lines.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations